On the complexity of boundary integral equations with analytic coefficients with logarithmic singularities - Azizov, M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We find the exact order of the ε-complexity of weakly singular integral equations with periodic and analytic coefficients of logarithmic singularities. This class of equations includes boundary equations for outer boundary-value problems for the two-dimensional Helmholtz equation.